2018
DOI: 10.1007/s40121-018-0194-1
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir-Associated Bone Adverse Outcomes among a US National Historical Cohort of HIV-Infected Veterans: Risk Modification by Concomitant Antiretrovirals

Abstract: IntroductionTenofovir disoproxil fumarate (TDF) has been associated with greater incidences of bone complications, which might be modified by some concomitantly administered antiretrovirals, possibly by their effect on tenofovir concentrations. We compared bone adverse outcomes among treatment-naïve HIV-infected US veterans initiating efavirenz (EFV)-containing TDF/emtricitabine (FTC) regimens versus those initiating non-EFV-containing TDF/FTC regimens.MethodsUsing national Veterans Health Administration clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Clinical trials and observational studies have shown an increase in CKD risk with regimens including TDF and boosted PIs (usually lopinavir or atazanavir) compared with regimens including TDF and NNRTIs [19–22]. In the Veterans Health Administration clinical and administrative datasets, PLWH taking efavirenz with TDF and FTC were significantly less likely to develop CKD than those taking elvitegravir/cobicistat and TDF [adjusted hazard ratio (aHR) = 0.75, 95% CI: 0.59–0.95) or a ritonavir‐boosted PI (aHR = 0.62, 95% CI: 0.53–0.72) [23]. In the Centers for AIDS Research Network of Integrated Clinical Systems cohort, PLWH taking TDF and a ritonavir‐boosted PI were more than three times more likely to develop stage 3–4 CKD compared with those taking neither TDF nor a pharmacoenhancer; the inclusion of either TDF or ritonavir‐boosted PI alone resulted in comparatively small and non‐significant increases in risk when compared with regimens that included neither [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical trials and observational studies have shown an increase in CKD risk with regimens including TDF and boosted PIs (usually lopinavir or atazanavir) compared with regimens including TDF and NNRTIs [19–22]. In the Veterans Health Administration clinical and administrative datasets, PLWH taking efavirenz with TDF and FTC were significantly less likely to develop CKD than those taking elvitegravir/cobicistat and TDF [adjusted hazard ratio (aHR) = 0.75, 95% CI: 0.59–0.95) or a ritonavir‐boosted PI (aHR = 0.62, 95% CI: 0.53–0.72) [23]. In the Centers for AIDS Research Network of Integrated Clinical Systems cohort, PLWH taking TDF and a ritonavir‐boosted PI were more than three times more likely to develop stage 3–4 CKD compared with those taking neither TDF nor a pharmacoenhancer; the inclusion of either TDF or ritonavir‐boosted PI alone resulted in comparatively small and non‐significant increases in risk when compared with regimens that included neither [24].…”
Section: Discussionmentioning
confidence: 99%
“…The potential for TDF nephrotoxicity may be enhanced by the concurrent administration of a pharmacoenhancer [19–22] due to elevations of tenofovir serum levels. Greater risks of developing CKD were observed with cobicistat‐boosted elvitegravir or a ritonavir‐boosted protease inhibitor (PI) than with efavirenz among PLWH on TDF [23]. In addition, combinations containing TDF with a ritonavir‐boosted PI have been associated with a greater risk of CKD compared with regimens that included neither TDF nor a pharmacoenhancer [24].…”
Section: Introductionmentioning
confidence: 99%
“…In a national cohort of US veterans, 33 048 treatment‐naïve PLWH without bone disease were commenced on tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) plus one of EFV ( n = 4137), elvitegravir/cobicistat (EVG/c) ( n = 232), rilpivirine (RPV) ( n = 171) or any one of three ritonavir‐boosted protease inhibitors (PIs) [atazanavir (ATV), lopinavir (LPV), or darunavir (DRV), n = 2621]. Those on EFV had significantly reduced risk of fragility fracture than all non‐EFV combined (aHR = 0.59, 95% CI: 0.44–0.78), RPV (aHR = 0.43, 95% CI: 0.31–0.61) and ritonavir‐boosted PIs (aHR = 0.6, 95% CI: 0.45–0.80) [55]. A similar study comparing fractures across FTC/TDF with EFV, RPV and EVG/c also identified a reduced risk of fracture with EFV compared with EVG/c; however, the authors concluded that the differences relate to pharmacodynamic differences, resulting in higher exposure to TDF as both cobicistat and RPV inhibit renal tubular transporters [11].…”
Section: Factors Associated With Fracturementioning
confidence: 99%
“…Some of the drugs that are used such as Efavirenz are related to a decrease of the 25-hydroxyvitamin D; Tenofovir is associated to secondary hyperparathyroidism, leading to an elevated bone turnover [21]; keeping in mind that these are fi rst line drugs, this creates a complicated outlook on the early management of infected patients. The side eff ects of some of the antiretroviral therapy, as protease inhibitors, and the main pathogenesis of the illness, cause kidney failure that is associated with proteinuria, leading to a low bone mineral density and elevated risk of fracture [22].…”
Section: Bone Mineral Densitymentioning
confidence: 99%